Revision of the Anotylus sculpturatus group (Coleoptera: Staphylinidae: Oxytelinae) with descriptions of seven new species from China - Wang, Lin-Fei; Zhou, Hong-Zhang; Lü, Liang (Zootaxa, 2017)
The Anotylus sculpturatus species group is one of the relatively well-defined assemblages within the very large genus Anotylus Thomson, 1859 of the subfamily Oxytelinae (Coleoptera: Staphylinidae). This paper briefly examines the species group classification of the genus Anotylus and concentrates mainly on the taxonomy of Anotylus sculpturatus group. The paper reviews the Chinese fauna of 13 species, with seven new species described here: Anotylus benisculptilis sp. nov., A. nigelisculptilis sp. nov. and A. brevisculptilis sp. nov. from Sichuan, A. varisculptilis sp. nov. from Yunnan and Sichuan, A. nitelisculptilis sp. nov. from Sichuan, Ningxia, Gansu and Shaanxi, A. rectisculptilis sp. nov. from Zhejiang, and A. extrasculptilis sp. nov. from Yunnan. Lectotypes are designated for Anotylus chinkiangensis (Bernhauer, 1938) and A. subsericeus (Bernhauer, 1938). Color figures and line-drawings are provided for all the new species and most of the earlier known species from China. A preliminary key to the species groups of Anotylus and a key to the species of Anotylus sculpturatus group, mainly focused on Chinese fauna, are also included in the paper, so as to benefit the classification and identification in the future.